PERANCANGAN SISTEM INFORMASI AKUNTANSI SIMPAN PINJAM MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI KOPERASI AS-SIROJI BANDUNG - sita apriliani; resmi ranti rosalina; pujiyanti putri lestari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research aims to design a savings and loan accounting information system usingMicrosoft Visual Studio 2010 at the As-Siroji cooperative in Bandung. Cooperatives arebusiness entities consisting of individuals or legal entities. As-Siroji Cooperative is anorganization as a member welfare unit. This cooperative is engaged in the field of savingsand loans, namely providing savings and loan services to members and cooperativeofficers. The method used is a qualitative method, with a descriptive approach and collectsdata by observation, interviews, documentation, and library studies. And the softwaredevelopment method used is the waterfall method. The problem that occurs in the As-SirojiCooperative is that the data recording in the As-Siroji Cooperative is all still manual usinga ledger which makes the work ineffective and prone to errors in data reporting. So fromthese problems, the authors provide suggestions, namely to make an information system inorder to accelerate the effectiveness of using the system, train cooperative staff who willuse the system, and this savings and loan information system must continue to bedeveloped, and maintained so that there is no damage to the system.